The effect of time and temperature on the shelf life of essential oils of Lavandula officinalis. Issue 5 (2nd September 2016) - Najafian, Sharareh
Abstract: Lavender ( Lavandula officinalis L.) has carminative, antispasmodic, antidepressant, expectorant, anti-rheumatic, relaxant, sedative, anti-inflammatory and tonic properties. It is a great aid for relaxing and winding down before bedtime. In this research the changes in the composition of essential oils from the aerial parts of Lavandula officinalis were determined at different temperatures and times. The essential oil of air-dried samples was obtained by hydro distillation and analyzed by gas chromatography/mass spectrometry (GC/MS). Changes in essential oils compositions were detected during storage for 4 months in refrigerator, freezer, and at room temperature. The results indicated that at room temperature, the proportions of compounds with lower boiling temperatures such as α -Pinene (2.3–0.2%), Camphene (1.5–0.1%), Sabinene (0.7–0.1%), β -Pinene (1.7–0.3%) and 1, 8-Cineole (24.7–16.2%) were decreased. Furthermore, the essential oil composition showed the least alterations and Lavandula officinalis L. kept its primary quality when stored at low temperatures, particularly in refrigerator.